2010
DOI: 10.1002/j.2161-1912.2010.tb00115.x
|View full text |Cite
|
Sign up to set email alerts
|

Vietnamese Immigrant and Refugee Women's Mental Health: An Examination of Age of Arrival, Length of Stay, Income, and English Language Proficiency

Abstract: Vietnamese immigrant and refugee women (N = 83) were surveyed regarding their mental health, English language proficiency, age of arrival, length of stay, and income. English language proficiency and age of arrival correlated with reduced symptomatology. Moreover, English language proficiency was the sole predictor of somatic distress.Se realizó una encuesta a un grupo de mujeres inmigrantes y refugiadas vietnamitas (N = 83) con respecto a su salud mental, nivel de inglés, edad de llegada, tiempo de estancia y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…Socio-demographic differences in the emotional health of the new refugees in this study were predominantly in keeping with previous research. Women had significantly increased odds of poor emotional well-being compared to men 7,18 and poor emotional well-being was associated with increasing age 9,19 . Younger refugees may find adjustment to a new culture and society easier, with increased behavioural flexibility aiding the acceptance of new values and customs 9,19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Socio-demographic differences in the emotional health of the new refugees in this study were predominantly in keeping with previous research. Women had significantly increased odds of poor emotional well-being compared to men 7,18 and poor emotional well-being was associated with increasing age 9,19 . Younger refugees may find adjustment to a new culture and society easier, with increased behavioural flexibility aiding the acceptance of new values and customs 9,19 .…”
Section: Discussionmentioning
confidence: 99%
“…Women had significantly increased odds of poor emotional well-being compared to men 7,18 and poor emotional well-being was associated with increasing age 9,19 . Younger refugees may find adjustment to a new culture and society easier, with increased behavioural flexibility aiding the acceptance of new values and customs 9,19 . The association between emotional well-being and country of origin may also reflect the varying nature of conflicts or political situations across the world and consequent variation in exposure to traumatic experiences.…”
Section: Discussionmentioning
confidence: 99%
“…16 Two main French charity organizations -the frame for the medical help. 17 The most often we can find the studies analyzing such topics as the health or the mental health of the refugees (Cernovsky 1988;Brown, Schale, Nilsson 2010;Crepet et al 2017;Centre Primo Levi 2018). 18 This is probably the most often researchers (even those who are mentioning the field study and ethnography) are working based on the interviews with the volunteers.…”
Section: Unusual State Of Artmentioning
confidence: 99%
“…Immigrants in the USA, for example, experience an increased risk of mental health disorders over time (Alegría et al, 2007;Breslau et al, 2007). Another study looking at Vietnamese immigrant women in the USA however, found no relationship between mental health and LoS (Brown et al, 2010). Further, among skilled workers in New Zealand and Turkish men (but not women) in Germany, mental health status appears to be positively related to LoS (Kotwal, 2010;Pernice et al, 2009).…”
Section: The Role Of Losmentioning
confidence: 99%